A socio-technical systems analysis of occupational health and safety hazards among municipal solid waste handlers: evidence from Sri Lankan urban municipalities - Geethmi Thisakya; Piumi Dissanayake (Facilities, 2026)
Purpose This study aims to systematically identify the underlying socio-technical causes of poor occupational health and safety (OHS) among municipal solid waste (MSW) handlers and their interactions using a systems-thinking approach to inform evidence-based interventions. Design/methodology/approach A multiple case study design was used across three urban municipal councils in Sri Lanka. Data were collected through semi-structured interviews with 21 participants, field observations and document reviews. The systems engineering initiative for patient safety (SEIPS) model was applied as the analytical framework to examine OHS hazards across six work system elements. Findings A total of 24 causal factors were identified across the work system: person (experience, education and health), task (manual handling and workload), tools and technology (ill-fitting personal protective and defective equipment), physical environment (weather and poor work conditions), organisation (inadequate supervision and insufficient training) and external environment (economic pressure, regulatory gaps and social stigma). Using the SEIPS model, a socio-technical framework is created to ensure a safe working environment for MSW handlers. Originality/value This research advances a comprehensive socio-technical framework for analysing OHS hazards in waste management. By revealing how system elements interact to generate compound risks, this study provides novel insights for developing integrated, multi-level interventions. It offers decision-makers a robust system-based understanding to enhance worker safety and strengthen safety management practices.